The Challenges of Literacy Culture in the Digital Era: The Role of Fairy Tales through the Country in Improving Literacy and Numerical Literacy - Bella Monica; Setiawan Edi Wibowo; Arta Mulya Budi Harsono (UIN Siber Syekh Nurjati Cirebon, 2023)
AbstractThis study aims to uncover (1) the challenges to foster literacy culture in the digital era, (2) the value of literacy conveyed through fairy tales, (3) the role of fairy tales for literacy and numeracy, and (4) the outcomes observed in literacy and numeracy development through fairy tales. The research used the qualitative approach with the case study method. Interviews, observations, and documentation were employed as data collection techniques. The collected data were analyzed through data collection, data reduction, data presentation, and drawing conclusions. The research results show that (1) the challenges of literacy culture in the digital era starts with finding and evaluating; (2) the literacy value conveyed through fairy tales includes literacy values encompassing listening, speaking, reading, and writing, while the value of numeracy includes skills in symbols and number, information analysis, and problem solving; (3) the role of fairy tales is as a medium to capture studentâ€™s attention. Fairy tales provide entertainment and moral teachings, which are engaging young learners since most children today prefer to see images rather than text. Therefore, the role of fairy tales is considered as a tool to enhance literacy among children.Keywords: fairy tales, literacy culture, numeracy.Â AbstrakPenelitian ini bertujuan untuk mengungkap (1) tantangan budaya literasi di era digital, (2) nilai literasi yang disampaikan melalui dongeng, (3) peran dongeng untuk literasi baca tulis dan numerasi, dan (4) hasil literasi dan numerasi melalui dongeng. Pendekatan penelitian menggunakan kualitatif dengan metode studi kasus. Penelitian ini menggunakan teknik pengumpulan data melalui wawancara, observasi, dan dokumentasi. Teknik analisis data berupa pengumpulan data, reduksi data, penyajian data dan penarikan kesimpulan. Hasil penelitian adalah (1) tantangan budaya literasi di era digital dimulai dengan menemukan dan mengevaluasi, (2) nilai literasi yang disampaikan melalui dongeng meliputi nilai literasi, yaitu menyimak, berbicara, membaca, dan menulis. Sedangkan nilai literasi numerasi adalah keterampilan simbol dan angka, menganalisis informasi, dan memecahkan masalah, (3) peran dongeng sebagai media untuk menarik perhatian peserta didik. Dongeng memberikan hiburan dan ajaran moral sehingga akan menarik bagi peserta didik untuk dilihat, karena sebagian besar anak saat ini lebih suka melihat gambar daripada teks. Oleh karena itu, peran dongeng dikatakan sebagai alat untuk meningkatkan budaya literasi kepada anak.Kata kunci: dongeng, budaya literasi, literasi numerasi.